Organizing Women in Contemporary Russia : Engendering Transition. - Sperling, Valerie (Cambridge University Press, 1999)
This book offers a rich and clearly-written analysis of the women's movement in contemporary Russia. It tells the engaging story of the women's movement's formation and development in a country undergoing a radical economic and political transition from communist rule.